Quail Agribusiness Entrepreneurship in Nigeria - Adebayo, Olaoluwa Ayodeji; Ademiluyi, Ibiyinka Olubukola; Akinola, Olufunlola Odunayo; Wahab, Munir Karounwi Adegoke (International Journal of Agriculture System, 2023)
Quail agribusiness entrepreneurship venture is a minimal expense, exceptionally simple and high benefit business. Up till now, the investment of agribusiness in quails is not yet famous. This study aimed to examine the quail agribusiness entrepreneurship in Nigeria. Cross-sectional data were obtained from 164 quail agribusiness entrepreneurs selected through a multi-stage sampling procedure. Descriptive and inferential statistics were used for data analysis. Results showed that the major motives for the agribusiness entrepreneurs' venture in quail agribusiness were that quail agribusiness and its egg production investment is profitable (23.78%). The technical information on quail production was mainly sourced from their associates/poultry-related agribusiness entrepreneurs (31.10%) and 59.76% had interactions with the agricultural extension officers while 40.85% obtained their funds to finance the quail agribusiness from their savings. The identified most prevalent constraint always faced by the quail agribusiness entrepreneurs include the inaccessibility to supply centres and markets (3.89) which necessitated the major training needs of quail meat processing and handling of quail eggs (26.22%). The study concluded that the age of the quail agribusiness entrepreneurs (r = 0.42; p≤0.05), their gross margin per production cycle (r = 0.85; p≤0.05) and their years of experience in quail agribusiness (r = 0.71; p≤0.05) are important contributors in determining the stock size of quails reared Nigeria. It was recommended that stakeholders in the quail agribusiness in Nigeria should improve their business capacity through collective capacity building/training programmes and awareness creation on production and the nutritional and medicinal value of quails.